Multidimensional poverty index and social determinants of health. Baseline for two vulnerable communities. - Germán Alberto Moreno-Gómez; María Beatriz Duarte-Gómez; Tonatiuh Barrientos-Gutiérrez (Revista de la Facultad de Medicina, 2017)
Introduction: Government policies and programs, aimed at reducing inequities, have a social and economic and impact on health conditions. However, they often lack evaluation processes that measure the impact of their interventions. Therefore, this study sets out a baseline of the Multidimensional Poverty Index (MPI) in two vulnerable communities, which will allow to assess the impact of development on a free zone. Materials and methods: Observational, descriptive and transversal study directed to establish the baseline of social determinants of health contained in the MPI, as well as the potential effect of the intervention on the variables and dimensions of the MPI in two precincts, before a free zone is developed. Results: Findings show the precarious living conditions and inequity in both populations, especially in the educational dimension, the rights of children and housing conditions. The variables that best explain poverty are illiteracy, education lag, and gravel floors which make habitability inappropriate. The prevalence of poverty in Caimalito (80.9%) and Puerto Caldas (66.5%) surpasses general poverty indexes in Colombia (24.8%) and in the central region (26.1%). Likewise, the adjusted incidence of poverty in Caimalito (20.1%) and Puerto Caldas (18.5%) is higher than in Colombia (13%). Conclusion: It is necessary to modify index variables that do not discriminate poor households. Simulation of isolated interventions have little or no effect on poverty reduction.